Trans-Anethole Alleviates DSS-Induced Ulcerative Colitis by Remodeling the Intestinal Flora to Regulate Immunity and Bile Acid Metabolism - Xu-Hui Li; Li Liu; Wen-Zhong Wu (Hindawi Limited, 2023)
Ulcerative colitis (UC) is the most common inflammatory bowel disease (IBD); it is incurable, and the treatment is expensive. Trans-anethole (TA), the main component of fennel, exhibits various biological activities. An increasing number of studies have demonstrated the efficacy of herbal active ingredients in the treatment of UC. This study aimed to investigate the effect and mechanism of TA in UC. In this study, we have experimented on mice with dextran sulfate sodium salt (DSS)-induced UC. The TA group was gavaged with 62.5 mg/kg TA by gavage once daily on days 8-14. To observe the effect of TA on the colon tissue, various investigations were performed, including western blot and immunohistochemistry for intestinal barrier protein expression, TUNEL staining for apoptosis, western blot, and ELISA for inflammation level, flow cytometry for Th17/Treg, LC-MS for blood bile acid content, GC-MS for blood fatty acid content, and 16s RNA for intestinal contents. TA alleviated weight loss in mice with UC; increased colon length; alleviated intestinal mucosal damage; upregulated claudin-1, occludin, and ZO-1 protein expression levels; reduced inflammatory factors in the colon and serum; and alleviated apoptosis. TA reduced fatty acid and bile acid levels by inhibiting colony abundance and reducing Th17/Treg cell differentiation in the colon. We found that TA alleviates DSS-induced UC by remodeling the intestinal flora to regulate immunity and bile acid metabolism.